Serine/Threonine Protein Kinase STK16 - Wang, Junjun (Int J Mol Sci, 2019)
STK16 (Ser/Thr kinase 16, also known as Krct/PKL12/MPSK1/TSF-1) is a myristoylated and palmitoylated Ser/Thr protein kinase that is ubiquitously expressed and conserved among all eukaryotes. STK16 is distantly related to the other kinases and belongs to the NAK kinase family that has an atypical activation loop architecture. As a membrane-associated protein that is primarily localized to the Golgi, STK16 has been shown to participate in the TGF-β signaling pathway, TGN protein secretion and sorting, as well as cell cycle and Golgi assembly regulation. This review aims to provide a comprehensive summary of the progress made in recent research about STK16, ranging from its distribution, molecular characterization, post-translational modification (fatty acylation and phosphorylation), interactors (GlcNAcK/DRG1/MAL2/Actin/WDR1), and related functions. As a relatively underexplored kinase, more studies are encouraged to unravel its regulation mechanisms and cellular functions.